Analisis Tingkat Kemampuan Literasi Digital pada Generasi Z di Kabupaten Sleman dalam Melakukan Transaksi di Shopee - Kirana, Dea Amanda Elta; Erwina, Wina; Rohman, Asep Saeful (Literatify: Trends in Library Developments, 2025)
The purpose of this study is to analyze the level of digital literacy among Generation Z in Sleman Regency in conducting transactions on Shopee. This research uses a descriptive quantitative approach with a purposive sampling technique. Data collection techniques come from primary data obtained through distributing questionnaires to 100 respondents, complemented by literature reviews and interviews to strengthen the evidence. The respondents of this study are Generation Z in Sleman Regency. The research findings reveal that the ability of Generation Z in Sleman Regency to use and disseminate information falls into the moderate category, accounting for 87%. The ability to create and collaborate is also in the moderate category, with 48%. The ability to analyze and evaluate falls into the high category, at 45%. Meanwhile, the ability to apply ethical judgment is categorized as moderate, with 93%. Overall, across the four core digital literacy skills, the majority of Generation Z in Sleman Regency who have conducted transactions on Shopee are categorized as moderate, representing 55%. This indicates that most Generation Z in Sleman Regency have fairly good digital literacy, although there remains a small portion with low digital literacy. Therefore, efforts to enhance digital literacy among Generation Z in Sleman Regency are still needed, as increased digital literacy is expected to improve security and awareness in using and optimizing digital platforms.